2016
DOI: 10.1177/1933719115611751
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anti-Müllerian Hormone in the Characterization of the Different Polycystic Ovary Syndrome Phenotypes

Abstract: Rotterdam criteria identified 4 polycystic ovary syndrome (PCOS) phenotypes based on the combination of anovulation (ANOV), hyperandrogenism (HA), and polycystic ovaries (PCOs): phenotype 1 (ANOV + HA + PCO), phenotype 2 (ANOV + HA), phenotype 3 (HA + PCO), and phenotype 4 (ANOV + PCO). Anti-Müllerian hormone (AMH) was suggested to play a pathophysiologic and diagnostic role in this syndrome. The aim of this study was to compare AMH levels among the different phenotypes in relation to clinical, endocrine, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
(66 reference statements)
5
13
0
Order By: Relevance
“…There is also some evidence that women with the PCOS phenotypes A and B have an increased risk of hepatic steatosis as compared with women with PCOS with the nonhyperandrogenic phenotype and compared with healthy controls (83,84). The highest antim€ ullerian hormone levels are also found in patients with classic PCOS (85)(86)(87). Data from 1,297 women with PCOS from Greece have shown that menstrual cycle pattern is more irregular in these women as compared with phenotype D but seems to normalize with ageing (88).…”
Section: ''Classic'' Pcos (Phenotypes a And B)mentioning
confidence: 99%
“…There is also some evidence that women with the PCOS phenotypes A and B have an increased risk of hepatic steatosis as compared with women with PCOS with the nonhyperandrogenic phenotype and compared with healthy controls (83,84). The highest antim€ ullerian hormone levels are also found in patients with classic PCOS (85)(86)(87). Data from 1,297 women with PCOS from Greece have shown that menstrual cycle pattern is more irregular in these women as compared with phenotype D but seems to normalize with ageing (88).…”
Section: ''Classic'' Pcos (Phenotypes a And B)mentioning
confidence: 99%
“…This difference might partly be related to epigenetic and environmental influences. Moreover, the free androgen index [34], serum AMH level [35][36][37][38], PPARGC1A (a leukocyte methylation promoter) [39], and some other indices were also found to be potential biomarkers for predicting PCOS and classifying its phenotypes. Although there have been many efforts to address the predicament surrounding the diagnosis of PCOS, the precise classification criteria have yet to be developed.…”
Section: Discussionmentioning
confidence: 98%
“…The difference might partly be related to the epigenetic and environmental influences. Moreover, the free androgen index (FAI) [34], serum anti-Müllerian hormone (AMH) level [35][36][37][38], PPARGC1A (a leukocyte methylation promoter) [39] and some other indexes were also found to be potential biomarkers for the prediction in women with PCOS and classification of its phenotypes. Although many efforts are spending on changing the predicament of clinical diagnosis, the precise classification criteria has yet to be developed.…”
Section: Discussionmentioning
confidence: 99%